Recrystallization of tubules from natural lotus (Nelumbo nucifera) wax on a Au(111) surface - Dora, Sujit Kumar; Wandelt, Klaus (Beilstein Journal of Nanotechnology, 2011)
We present here the first results on the self-assembly of tubules of natural wax from lotus leaves on a single crystal Au(111) surface. A comparison of the tubule growth on Au(111) to that on HOPG is discussed. Although the tubule formation on both Au(111) and HOPG takes place on an intermediate wax film which should mask the substrate properties, the tubule orientations differ. In contrast to a vertical tubule orientation on HOPG, the tubules lie flat on Au(111). Taking into account the physical properties of HOPG and Au(111), we put forward a hypothesis which can explain the different tubule orientations on both substrates.
Keywords: AFM; Au(111); lotus wax

Self-assembly and pattern formation of epicuticular waxes on plant surfaces - Dommisse, A. (2007)

(untitled) - Jetter, R.; Riederer, M. (Planta, 1994)

(untitled) - Matas, A. J.; Sanz, M. J.; Heredia, A. (Int. J. Biol. Macromol., 2003)

(untitled) - Niemietz, A.; Wandelt, K.; Barthlott, W.; Koch, K. (Prog. Org. Coat., 2009)

(untitled) - Koch, K.; Bhushan, B.; Barthlott, W. (Prog. Mater. Sci., 2009)

(untitled) - Koch, K.; Dommisse, A.; Niemietz, A.; Barthlott, W.; Wandelt, K. (Surf. Sci., 2009)

(untitled) - Barthlott, W.; Neinhuis, C.; Cutler, D.; Ditsch, F.; Meusel, I.; Theisen, I.; Wilhelmi, H. (Bot. J. Linn. Soc., 1998)

(untitled) - Koch, K.; Dommisse, A.; Barthlott, W. (Cryst. Growth Des., 2006)

Springer Handbook of Nanotechnology - Koch, K.; Bhushan, B.; Barthlott, W. (Multifunctional Plant Surfaces and Smart Materials, 2010)

(untitled) - Ensikat, H. J.; Boese, M.; Mader, W.; Barthlott, W.; Koch, K. (Chem. Phys. Lipids, 2006)

(untitled) - Malkin, T. (Progr. Chem. Fats Other Lipids, 1952)

(untitled) - Cousty, J.; Marchenko, A. (Surf. Sci., 2002)

(untitled) - Marchenko, A.; Cousty, J. (Wear, 2003)

(untitled) - Heinz, B.; Morgner, H. (Surf. Sci., 1997)

(untitled) - Balzer, F.; Gerlach, R.; Polanski, G.; Rubahn, H. G. (Chem. Phys. Lett., 1997)

(untitled) - Jin, Q.; Rodriguez, J. A.; Li, C. Z.; Darici, Y.; Tao, N. J. (Surf. Sci., 1999)

(untitled) - Suto, K.; Yoshimoto, S.; Itaya, K. (J. Nanosci. Nanotechnol., 2009)

(untitled) - Resta, A.; Felici, R.; Kumar, M.; Pedio, M. (J. Non-Cryst. Solids, 2010)

(untitled) - Mayer, D.; Dretschkow, T.; Ataka, K.; Wandlowski, T. (J. Electroanal. Chem., 2002)

(untitled) - Böhringer, M.; Morgenstern, K.; Schneider, W.; Wühn, M.; Wöll, C.; Berndt, R. (Surf. Sci., 2000)

(untitled) - Ivanova, V.; Buess-Hermann, C. (J. Electroanal. Chem., 2003)

(untitled) - Zhu, N.; Osada, T.; Komeda, T. (Surf. Sci., 2007)

(untitled) - Lee, Y.; Chang, C.; Yau, S.; Fan, L.; Yang, Y.; Yang, L.; Itaya, K. (J. Am. Chem. Soc., 2009)

(untitled) - Watel, G.; Thibaudau, F.; Cousty, J. (Surf. Sci., 1993)

(untitled) - Dorset, D. L. (Acta Crystallogr., Sect. B, 1995)

(untitled) - Dorset, D. L.; Pangborn, W. A.; Hancock, A. J. (J. Biochem. Biophys. Methods, 1983)

(untitled) - Koch, K.; Barthlott, W.; Hommes, A.; Wandelt, K.; Mamdouh, W.; De-Feyter, S.; Broekmann, P. (Planta, 2005)

(untitled) - Sarraf, H.; Skarpova, L.; Louda, P. (Arch. Mater. Sci. Eng., 2007)

(untitled) - Kusunoki, K.; Sakata, I.; Miyamura, K. (Anal. Sci., 2001)

(untitled) - Sanfelix, P. C.; Holloway, S.; Kolasinski, K. W.; Darling, G. R. (Surf. Sci., 2003)

(untitled) - Papadantonakis, K. M.; Brunschwig, B. S.; Lewis, N. S. (Langmuir, 2008)

(untitled) - Koch, R. (J. Phys.: Condens. Matter, 1994)

(untitled) - Huang, M.; Boone, C.; Roberts, M.; Savage, D. E.; Lagally, M. G.; Shaji, N.; Qin, H.; Blick, R.; Nairn, J. A.; Liu, F. (Adv. Mater., 2005)

(untitled) - Zang, J.; Huang, M.; Liu, F. (Phys. Rev. Lett., 2007)

Untersuchungen zum Adsorptionsverhalten molekularer Filme epikutikularer Wachse auf artifiziellen Oberflächen - Hommes, A. (University Bonn, 2010)